COLLECTIVE WORKING AGREEMENTS (CLA) IN A JURIDICAL AND PRACTICAL - Prayitno, Sugeng; Wawan Kurniawan (Pasundan International of Community Services Journal (PICS-J), 2024)
The emergence of a work relationship between the employer and the employee is based on the existence of an employment agreement. The employment agreement is one of the derivatives of the agreement in general, where each agreement has special characteristics that distinguish it from other agreements. In the implementation of work agreements between employers and workers, it often causes basic problems, where the basic problem is that it is not accommodated related to the fulfillment of rights and obligations between workers and employers. an effective, transparent and accountable work agreement in accordance with the laws and regulations, one of which is a Collective Labor Agreement (PKB). The employment relationship occurs after the employment agreement, and the employment agreement is a legal event, so that the consequences of an employment relationship cause legal consequences in the form of rights and obligations for the parties.